Experimental characterization of temperature dependent dynamic properties of glass fiber reinforced polyurethane foams. (April 2019) - Lee, Dong-Ju; Kim, Min-Kyeom; Walsh, Joseph; Jang, Hong-Kyu; Kim, Hyung-Ick; Oh, Eun-Young; Nam, Jaedo; Kim, Myunghyun; Suhr, Jonghwan
Abstract: The static and dynamic compressive behaviors of glass fiber-reinforced polyurethane foams were characterized under cryogenic temperature conditions to help identify the essential design and parameters required to model the response of the foam accurately under the various loading conditions encountered in liquefied natural gas cargo containment systems. The material properties of polyurethane foams with varying concentrations and orientations of the glass fiber continuous strand mat were characterized by quasi-static, dynamic mechanical analysis (DMA), and low velocity impact testing. The testing results showed increased strength with increasing density and strain rate, as well as similar failure modes independent of the strain rate. In addition, the glass fibers dominated the DMA behavior and a glass transition temperature at or above 130 °C was observed for all foam varieties. Overall, the glass fiber reinforced polyurethane foam showed the typical static and dynamic compressive behaviors of foams at both room and cryogenic temperatures. Highlights: The static and dynamic viscous behaviors of the glass fiber-reinforced polyurethane foams (PUFs) were characterized by the quasi-static and dynamic tests. The glass fiber-reinforced polyurethane foams were fabricated with varying concentrations and orientations of the glass fiber continuous strand mat (CSM). Through the quasi-static test, it was observed that the fracture of the fibers may occur depending on the direction of CSM. Low velocity impact test showed the rate dependent stress-strain relationship with the various densities. The viscoelastic responses of the PUF specimens with different densities were examined by DMA test.